Exploratory talks and peace initiatives in Afghanistan: Actors, demands, Germany's role as mediator - Nils Wörmer (Stiftung Wissenschaft und Politik (SWP), 2012)
It is widely held that NATO's strategy in Afghanistan can only succeed if progress is made in the country's internal peace process. But none of the initiatives to date have been able to initiate meaningful negotiations, nor has it been possible to reach lasting agreements on representatives, mediators, topics and procedures. Numerous actors have already been involved in exploratory talks involving both independent and interconnected threads. It would represent an important step forward if existing initiatives could be channelled into an orderly negotiating process. Germany can play an important mediating role here. Talks about a political resolution of the Afghanistan conflict will be protracted and complex, their outcome open. Forward strategic thinking must also consider the possibility of the Afghan peace process failing
Keywords: 320